2006
DOI: 10.2343/geochemj.40.245
|View full text |Cite
|
Sign up to set email alerts
|

Helium isotopic composition of hydrothermal fluids from the Manus back-arc Basin, Papua New Guinea

Abstract: We present isotopic analysis of helium in hydrothermal fluids from the Manus back-arc basin, collected during the French-Japanese Manusflux and Manaute cruises in 1995 and 2000, respectively. The helium isotope composition of the fluids is comparable to that measured elsewhere in similar subduction environments, with 3 He/ 4 He values (7.4 to 7.9 R a ) slightly lower than typical MORB values, except on the Manus Spreading Center (MSC) where higher values (12 ± 0.1 R a ) are observed. The causal link between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Despite being located 100-150m apart, the three fluids exhibited a narrow range of temperatures (273-285°C) and compositions (Tables 5.1 and 5.2) suggesting that the Vienna Woods field is fed by a common source fluid. Measured temperatures, pH (25C) and endmember fluid composition have remained relatively constant since previous expeditions in 1990 and 1995 (Lisitsyn et al, 1993;Auzende et al, 1996;Gamo et al, 1997;Douville et al, 1999;Fourre et al, 2006). In general, almost all aspects of the chemistry of fluids venting at Vienna Woods are similar to observations from basalt-hosted hydrothermal systems in MOR settings (Von Damm, 1995;German and Von Damm, 2003).…”
Section: Temperaturesupporting
confidence: 65%
See 1 more Smart Citation
“…Despite being located 100-150m apart, the three fluids exhibited a narrow range of temperatures (273-285°C) and compositions (Tables 5.1 and 5.2) suggesting that the Vienna Woods field is fed by a common source fluid. Measured temperatures, pH (25C) and endmember fluid composition have remained relatively constant since previous expeditions in 1990 and 1995 (Lisitsyn et al, 1993;Auzende et al, 1996;Gamo et al, 1997;Douville et al, 1999;Fourre et al, 2006). In general, almost all aspects of the chemistry of fluids venting at Vienna Woods are similar to observations from basalt-hosted hydrothermal systems in MOR settings (Von Damm, 1995;German and Von Damm, 2003).…”
Section: Temperaturesupporting
confidence: 65%
“…As stated previously, Mn abundances in Vienna Woods fluids only suggest temperatures near 350°C and so it is possible that the high Cl endmembers do not reflect active phase separation at depth in 2006, but rather entrainment/depletion of residual brines formed during previous phase separation events (Shanks and Seyfried, 1987;Von Damm and Bischoff, 1987;Von Damm, 1988;Butterfield et al, 1997;Schoofs and Hansen, 2000;Von Damm et al, 2005). Brine entrainment would be consistent with the chronic venting of Cl-rich fluids at Vienna Woods since 1990 (Lisitsyn et al, 1993;Auzende et al, 1996;Gamo et al, 1997;Douville et al, 1999;Fourre et al, 2006) and the apparent absence of any Cl-depleted conjugate fluids.…”
Section: Phase Separation and CL Variabilitymentioning
confidence: 81%
“…EMZV in (a) indicates the location of the Eastern Manus Volcanic Zone. Douville et al, 1999a,b;Gena et al, 2001Gena et al, , 2006Fourre et al, 2006). Fluids samples were collected during this study at two sites (D1 and D2; Fig.…”
Section: Desmos Calderamentioning
confidence: 99%
“…5; we have not plotted the Alice Springs field because we lack data for He . Those reported for the Valu Fa Ridge in the Lau Basin (Takai et al, 2008), the Manus Spreading Center and Pual Ridge in the Manus Basin (Fourre et al, 2006), the White Lady site in the North Fiji Basin (Ishibashi et al, 1994b), Suiyo Seamount in the Izu-Bonin Arc (Tsunogai et al, 1994), northwest caldera sites in Brothers Seamount in the Kermadec Arc (de Ronde et al, 2011), and for hydrothermal fields in the North and South-East Pacific Rise (Merlivat et al, 1987;Jean-Baptiste et al, 1997) are also shown.…”
Section: Gas Geochemistrymentioning
confidence: 86%
“…4. In the same figure, the ratios from other arc-backarc systems in the western Pacific, the Valu Fa Ridge (VFR) in the Lau Basin (Takai et al, 2008), the Pual Ridge and Manus Spreading Center in the Manus Basin (Fourre et al, 2006), the White Lady site in the North Fiji Basin (Ishibashi et al, 1994b), Suiyo Seamount in the Izu-Bonin Arc (Tsunogai et al, 1994) (Sano et al, 1998). These ratios are within the typical range of MORB ( 3 He/ 4 He ¼8 71R/R A ) and are similar to those of the EPR hydrothermal fluids (Fig.…”
Section: Gas Geochemistrymentioning
confidence: 91%